Análisis de los costos de venta y gastos operacionales de la sociedad Emflusa empresarios Fluminenses S.A. - Reasco Gavilanes, Rogger Kenny (2019)
This research work has as its theme “Analysis of the sales costs and operational expenses of the company Emflusa Empresarios Fluminenses S.A.”, which are intended to support and generate income. An analysis of the sales costs and operating expenses of the 2018 period will be carried out, in order to identify the existing impact of these, with respect to the usefulness of the period, because the companies that are engaged in the activity of selling fuel they were affected by the elimination of the subsidy for certain fuels and this makes their costs and expenses more expensive, significantly reducing their sales and thus running the risk of not covering their costs and operating expenses